1993
DOI: 10.1172/jci116340
|View full text |Cite
|
Sign up to set email alerts
|

N-3 fatty acids stimulate intracellular degradation of apoprotein B in rat hepatocytes.

Abstract: When rat hepatocytes were incubated with albumin complexed to the n-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), rather than to oleic acid (OA), the secretion of newly synthesized apoprotein B100 (apoB100) or B48 (apoB48) was reduced, despite stimulation of cellular triglyceride synthesis by all three fatty acids. When pulse-chase studies of apoB synthesis and secretion were performed in the presence of OA, EPA, or DHA, there were no significant changes in the initial synthetic ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
95
3
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 44 publications
5
95
3
1
Order By: Relevance
“…In addition, the effect of PUFAs on total apoB48 recovery has been small in prior and the present studies (data not shown), owing to its under-representation in large lipid-rich particles (8,48). As indicated in Results, depending on the experiment, either the total amount of labeled apoB100 (intracellular plus secreted) or the separate recoveries from cells or conditional media were determined by immunoprecipitation followed by SDS/PAGE/fluorography/densitometry, as described in ref.…”
Section: Methodscontrasting
confidence: 60%
“…In addition, the effect of PUFAs on total apoB48 recovery has been small in prior and the present studies (data not shown), owing to its under-representation in large lipid-rich particles (8,48). As indicated in Results, depending on the experiment, either the total amount of labeled apoB100 (intracellular plus secreted) or the separate recoveries from cells or conditional media were determined by immunoprecipitation followed by SDS/PAGE/fluorography/densitometry, as described in ref.…”
Section: Methodscontrasting
confidence: 60%
“…Plasma and liver TAG concentrations were significantly lower in the CϩEX, KBR, and DF/KBRϩEX groups in comparison to the C group, data which are in agreement with reports that n-3 polyunsaturated fatty acid (PUFA) lowers plasma TAG concentration by decreasing hepatic TAG (45,46). Since most fish oils contain more EPA than DHA, EPA may contribute to reduced plasma TAG concentration (47).…”
Section: Discussionsupporting
confidence: 89%
“…Thus, apoB mRNA levels are relatively stable under many conditions, whereas secretion of apoB-containing lipoproteins is altered (1)(2)(3)(4)(5). The impact of this posttranslational regulation is demonstrated by the observations that only a small to moderate proportion of the newly synthesized apoB is eventually secreted from primary rat hepatocytes (6,7), McArdle cells (8), and HepG2 cells (9). A major portion of newly synthesized apoB undergoes rapid intracellular degradation in a pre-Golgi or ER compartment (10 -12) in HepG2 cells as well as in apoB cDNA-transfected Chinese hamster ovary cells (13).…”
Section: Apobmentioning
confidence: 99%